Gas oversaturation in deep coals and its implications for coal bed methane development: A case study in Linxing Block, Ordos Basin, China - Kang, Yongshang; Huangfu, Yuhui; Zhang, Bing; He, Zhiping; Jiang, Shanyu; Ma, Yuan Zee (Frontiers in Earth Science, 2023)
Three coal bed methane (CBM) wells penetrating to coal seams 8+9# (Permian Taiyuan Formation), in deep coals (depth>1,500m), show very differential production performance in Linxing Block, eastern margin of the Ordos Basin in China. The mechanism for the performance differentiation is analyzed through studies on coal permeability and gas saturation in deep coals, and specifically, the comparison of coal reservoir characteristics in the three wells. The mechanism for gas oversaturation is then discussed based on data from Linxing Block and spot but important exploration results relevant to deep coals in the Junggar Basin. This study demonstrates that: (1) Permeability values of coal seams 8+9# in deep coals are probably in the order of 10-2mD from diverse sources including results of experimental permeability test simulating underground stress conditions. Studies on gas saturation distribution reveal that high gas rates (>3,000m3/d) can be achieved only from oversaturated coal reservoirs in Linxing Block. (2) Two types of oversaturation mechanism, including igneous intrusion-driven oversaturation and sorption capacity-driven oversaturation, exist in deep coals. The former is restricted to regions/blocks influenced by igneous intrusion, and characterized by secondary gas generation and supplementation to deep coals that have substantial similar Langmuir curves to that of shallow coals. The latter may play in deep coals that are not influenced by igneous intrusion, and is characterized by more free gas released from coals after adsorption saturation, due to reduced sorption capacity in deep coals; (3) Oversaturation may exist more frequently in deep coals (in comparison with shallow coals), due to mostly the sorption capacity-driven oversaturation mechanism, and the weaker tectonic deformation and uplifting experienced by deep coals in comparison with shallow coals, which favors gas preservation and oversaturation. (4) Generally, coal permeability in deep coals is low due to the increased effective stress, and exploring oversaturation areas should be a primary concern for CBM development. It appears that in most large, tectonically compressed coal basins, there is a critical depth beyond which the oversaturation areas could occur, presenting opportunities and challlenges for CBM development.